2003
DOI: 10.1103/physrevlett.90.228303
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Profiles in Shear-Banding Wormlike Micelles

Abstract: Using Dynamic Light Scattering in heterodyne mode, we measure velocity profiles in a much studied system of wormlike micelles (CPCl/NaSal) known to exhibit both shear-banding and stress plateau behavior. Our data provide evidence for the simplest shear-banding scenario, according to which the effective viscosity drop in the system is due to the nucleation and growth of a highly sheared band in the gap, whose thickness linearly increases with the imposed shear rate. We discuss various details of the velocity pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
205
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 209 publications
(232 citation statements)
references
References 27 publications
19
205
3
1
Order By: Relevance
“…During the transition from linear to 3-banded profiles (for imposed shear rates ofγ = 0.3 s −1 andγ = 0.45 s −1 ) the material exhibits an intermediate behavior in which the flow profile appears to have two developing shear bands instead of three clearly distinct bands. This is in contrast to some shear banding scenarios which have been observed in other geometries (such as those observed by Salmon et al (2003) in Couette flow) where the shear rate in the highly sheared band remains constant and the interface between the low and high shear rate regions moves as the apparent shear rate is increased. The data presented in Figure 5 was obtained without the plano-concave lens in place, and with the upper and lower geometries being covered by the transparent film.…”
Section: Steady Shear Rate Banding Of Cpyclcontrasting
confidence: 50%
See 4 more Smart Citations
“…During the transition from linear to 3-banded profiles (for imposed shear rates ofγ = 0.3 s −1 andγ = 0.45 s −1 ) the material exhibits an intermediate behavior in which the flow profile appears to have two developing shear bands instead of three clearly distinct bands. This is in contrast to some shear banding scenarios which have been observed in other geometries (such as those observed by Salmon et al (2003) in Couette flow) where the shear rate in the highly sheared band remains constant and the interface between the low and high shear rate regions moves as the apparent shear rate is increased. The data presented in Figure 5 was obtained without the plano-concave lens in place, and with the upper and lower geometries being covered by the transparent film.…”
Section: Steady Shear Rate Banding Of Cpyclcontrasting
confidence: 50%
“…This approach is reasonable because it is well known that when viscometric approximations hold, spatial variations in the stress in a cone-plate geometry are very small (Bird et al, 1987). Subsequent velocimetric studies have focused more often on observing banding in cylindrical Couette geometries (Salmon et al, 2003;Manneville et al, 2004a;Miller and Rothstein, 2007). These velocimetry studies have shown that there is a clear difference between the structure of the shear-banded profiles observed in the two cases.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations